Mediating effect of purchasing efficiency on the relationship between purchasing analytical skills and restaurant performance: a PLS-SEM approach - Ismail Abdi Changalima; Ruth Elias (Journal of Money and Business)
Purpose – This study analyzes the mediating effect of purchasing efficiency on the relationship between purchasing analytical skills and restaurant performance. Design/methodology/approach – A structured questionnaire was used to collect data from 169 restaurant managers in Dodoma, Tanzania. The collected data were analyzed by using partial least squares structural equation modeling (PLS-SEM). Findings – The results established the direct and indirect effects of purchasing analytical skills on restaurant performance. Specifically, purchasing analytical skills have positive and significant effects on restaurant performance and purchasing efficiency. Also, purchasing efficiency significantly mediates the effect of purchasing analytical skills on restaurant performance. Since purchasing analytical skills significantly influence restaurant performance, and the mediating effect of purchasing efficiency is significant, the study establishes and confirms the partial mediation effect of purchasing efficiency. Research limitations/implications – The current study solely focused on purchasing analytical skills. Future studies may examine other types of purchasing skills (technical and managerial skills) to expand the study's findings. Furthermore, different mediating variables can be used to study the indirect effect of purchasing analytical skills on restaurant performance. Originality/value – This study presents empirical evidence from Tanzania, an emerging economy, on the link between purchasing analytical skills and restaurant performance. It also contributes to the body of knowledge by studying the mediating effect of purchasing efficiency in the hypothesized relationship.